The Impact of Open-Ended Learning on 21st-Century Skill Acquisition in Early Learners - Puji, Chintya; Hakobyan, Aram (Journal of Early Childhood Education and Teaching (JECET), 2025)
Purpose – This study aims to evaluate the effectiveness of an open-ended learning model based on 21st-century skills in enhancing the learning experiences of early childhood learners. In today’s dynamic educational landscape, integrating critical thinking, creativity, communication, and collaboration into early learning is essential to prepare children for future challenges.Design/methods/approach – The research employed a quantitative method using structured questionnaires distributed through Google Forms to early childhood educators. Data were collected in numerical form and analyzed using SPSS, with results displayed through tables and graphs. The approach enabled a comprehensive assessment of how the open-ended learning model supports the development of 21st-century skills in young children. Findings – The findings show that the open-ended learning model based on 21st-century skills is effective in enhancing early childhood learners’ engagement and skill acquisition. Children demonstrated improvements in critical thinking, problem-solving, and communication. The model created opportunities for children to express ideas creatively and independently through open problem-solving activities. Research implications/limitations – This study is limited by its small sample size and focused context. Further research should explore long-term implementation across various settings and include observational data to support self-reported measures. Originality/value – This research offers valuable insights into the application of open-ended learning in early childhood education. It underscores the importance of integrating 21st-century skills into early learning practices and provides educators with practical strategies for fostering creativity, collaboration, and independent thinking in young learners.